HUBUNGAN KEPERCAYAAN DIRI DENGAN PERILAKU PROSOSIAL ANAK USIA 5-6 TAHUN - Amanda Wulandari; Daviq Chairilsyah; Yeni Solfiah (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
The study aims to determine the level of relation between confidence and prosocial behavior of children aged 5-6 years in TK Negeri Pembina 2 Kota Pekanbaru. The samples in this research are children aged 5-6 years old in TK Negeri Pembina 2 Kota Pekanbaru which amounted to 80 children. The method used in this study is a quantitative correlation. The data collection techniques used are by observation. Data analysis techniques Use the correlation test Person Product moment with IBM SPSS Versi 23 program. From the research results known confidence levels are in the medium (56,58%) and the level of the child's prosocial behavior is in a medium (57,75%). Based on the hypothesis test results obtained there is a positive and significant relationship between the confidence with the prosocial behavior of children aged 5-6 years in TK Negeri Pembina 2 Kota Pekanbaru and the value of the correlation coefficient of rxy = 0,690 and the value of the coefficient of determination resulting from KD = 47,61% has the meaning that the confidence affects 47% of the prosocial behavior.